Eucalyptus camaldulensis in South Africa – past, present, future. Issue 1 (2nd January 2020) - Hirsch, Heidi; Allsopp, Michael H.; Canavan, Susan; Cheek, Michael; Geerts, Sjirk; Geldenhuys, Coert J.; Harding, Graham; Hurley, Brett P.; Jones, Wayne; Keet, Jan-Hendrik; Klein, Hildegard; Ruwanza, Sheunesu; et al.
Abstract : Eucalyptus camaldulensis can be seen as an iconic tree of superlatives. It is the eucalypt with the widest native range, and one of the most widely planted eucalypts around the globe. In South Africa, it is the most widespread and the most aggressively invasive eucalypt. It has many uses, but also causes major impacts. However, little is known about key aspects of its ecology in South Africa, including its invasion history, invasion processes and dynamics, and people's perceptions of its positive and negative effects on ecosystems. Such knowledge is crucial for developing robust and defendable guidelines for sustainable management of the species. This paper provides a comprehensive dossier of the species in South Africa. It reviews what is known of its introduction and planting history, its current distribution, its value for commercial forestry and other uses, its impacts as an invasive species, pests and pathogens associated with the species, people's perceptions of the species and conflicts of interest, and the options for management and restoration. The review reveals that E. camaldulensis is a tree of many contradictions in South Africa, making it a poster-child example of a conflict-generating non-native species. Based on available knowledge, we assess options for improved management. We highlight several knowledge gaps which need to be addressed in more detail through future research. It is hoped that this species profile will serve as a model for the types of information that are needed for developing objective management strategies for non-native tree species in different parts of the world.